Potential of turmeric cream (curcuma caesia roxb.) extract in incision wounds - Ni Nyoman Wahyu Udayani; I Ketut Agus Adrianta; I Putu Bagus Artha Wiguna; Anak Agung Sagung Iswarani Yowani (Medisains)
Background: Incisional wounds are the most common wounds in the community. Improper handling of incision wounds can worsen wounds and cause infection. The content of secondary metabolites in black turmeric rhizomes can act as anti-inflammatory and antimicrobial in the healing process of incision wounds. However, its effectiveness in healing incision wounds has not been widely studied, so further research is needed.